Transparency of nuclear regulatory activities : Workshop proceedings Tokyo and Tokai-Mura, Japan 22-24 May 2007 - Organisation for Economic Co-operation and Development (Paris : OECD, 2007)
Understanding transparency -- Stakeholder expectations regarding transparency -- Conditions for ensuring transparency -- Changing regulatory practices for ensuring transparency -- Methods for evaluating transparency.
'Organised in collaboration with the Japan Nuclear and Industrial Safety Agency and the Japan Nuclear Energy Safety Organisation.'
'NEA No. 6256.'
Includes bibliographical references
Keywords: Nuclear energy -- Law and legislation -- Congresses; Nuclear energy -- Public opinion -- Congresses; Nuclear industry -- Safety measures -- Congresses; Nuclear industry -- Decision making -- Congresses